Myofibrillar Protein, Lipid and Myoglobin Oxidation, Antioxidant Profile, Physicochemical and Sensory Properties of Caprine longissimus thoracis during Postmortem Conditioning. Issue 4 (5th September 2016) - Adeyemi, Kazeem Dauda; Shittu, Rafiat Morolayo; Sabow, Azad Behnan; Karim, Roselina; Sazili, Awis Qurni
Abstract: The study examined the impact of refrigerated storage on antioxidant profile, oxidative changes in myoglobin, lipids and myofibrillar proteins and quality attributes of longissimus thoracis (LT) muscle from goats. Analyses were conducted on LT obtained from carcasses of sixteen Boer bucks on 0, 1, 5 and 10 days postmortem . Ageing had no effect on antioxidant enzyme activities. Concentration of tocopherols and total carotenoids decreased over storage. Myoglobin, metmyoglobin reducing activity, redness and shear force decreased while metmyoglobin content and drip loss increased over storage. Free thiol decreased while carbonyls and TBARS increased over storage. The relative density of myosin heavy chain, actin and troponin T and the concentration of n −6 and n −3 fatty acids were stable until day 5 but declined afterward. Tocopherol and carotenoid were correlated ( P < 0.05) with oxidative changes. Ageing did not affect consumer preference for juiciness, flavor and overall acceptability. However, preference for tenderness increased over storage. Practical Applications: Information on the impact of postmortem ageing on the antioxidant status of chevon in relation to its oxidative changes, physicochemical properties and shelf life is limited. This study demonstrates that although tenderness improved, quality loss during ageing of chevon is inexorable. The tocopherols and carotenoids are the primary drivers of postmortem oxidative stability of chevon. Antioxidant enzymes do not seem to play a significant role in the postmortem oxidative stability of chevon. The oxidative stability of longissimus thoracis in goats could be maintained for 5 days during chill storage. The current findings would provide useful information to consumers, retailers and meat industries on the merits and demerits of postmortem ageing of chevon and the factors to consider when longer ageing periods are desired or necessitated.